Accuracy of 12‐hour urine collection in the diagnosis of pre‐eclampsia. Issue 3 (13th June 2018) - Silva, Rita M.; Pereira, Sara R.; Rego, Susana; Clode, Nuno
Abstract: Objective: To evaluate the accuracy of a 12‐hour urine collection to diagnose pre‐eclampsia and to determine whether time of collection influences the performance of this test. Methods: A prospective observational study was conducted in a tertiary obstetric center in Portugal between November 1, 2015, and November 30, 2016. Pregnant women (≥20 weeks) admitted for observation with suspected pre‐eclampsia were eligible for inclusion. Two consecutive 12‐hour urine samples were collected (07:00–19:00 hours vs 19:00–07:00 hours). Protein levels were measured in each 12‐hour sample, as well as in a pooled sample (07:00–07:00 hours). The diagnostic cut‐off values for pre‐eclampsia were 150 mg (12‐hour samples) and 300 mg (24‐hour sample). Results: The study included 99 patients and diagnoses of pre‐eclampsia were confirmed among 42 (42%) patients. In all, 456 12‐hour urine samples were analyzed (equivalent to 228 24‐hour samples). Qualitative analysis (pre‐eclampsia vs no pre‐eclampsia) indicated substantial agreement between the 12‐ and 24‐hour samples (Cohen κ 0.779). The sensitivity was 85.9% (95% confidence interval [CI] 81%–90%) and the specificity was 91.7% (95% CI 88%–95%). No statistically significant difference was found between the two 12‐hour collections. Conclusion: The 12‐hour test showed acceptable accuracy for detecting pre‐eclampsia, regardless of the time of collection. Abstract : A 12‐hour urine collection offered an alternative to a 24‐hour urine collection for diagnosis of pre‐eclampsia owing to acceptable accuracy in the detection of proteinuria.